How can molecular chaperones repair damaged protein structures? - Goloubinoff, Pierre (Henry Stewart Talks, 2021)
The role of molecular chaperones, Concept of polypeptide unfolding enzymes, The RubisCO binding protein, Molecular chaperones can proof-read the quality of protein folding, structure and function of Hsp70, The folding state of Hsp70 substrate, Substrate targeting, Entropic pulling, J-domain cochaperones